STRATEGI PENGUATAN BUDAYA ETIK BERLALU LINTAS - Vita Mayastinasari; Benyamin Lufpi; Novi Indah Earlyanti (Journal of Indonesia Road Safety, 2018)
His research aims to recommend a strategy to strengthen the ethical culture of traffic that is expected to provide output in the form of: The realization of security, safety, order, smooth traffic; Realizing the positive performance of the police institution; Improving the quality of life of the community. The results of the study are also expected to accelerate the integration between units in the traffic function in order to realize the optimization of police traffic performance, efficiency and effectiveness of traffic police performance and optimization of road safety so as to reduce: the number of traffic accidents, potential security and road safety and congestion disruptions traffic.The focus of the study includes: Traffic violations; Constraints to realizing Security, Safety, Order, Smooth Traffic (Kamseltibcarlantas); Strategies for strengthening the ethical culture of traffic to realize Kamseltibcarlantas. Various obstacles to realizing Security, Safety, Order, Smooth Traffic (Kamseltibcarlantas) cover several aspects, namely: regulation, availability of public transportation, databases and information technology. Some strategies that can be developed related to strengthening the ethical culture of traffic are: a) Determination of regulations related to reward and punishment of traffic violators; b) Provision and development of safe public transportation; c) Integration of data and systems; d) Integrated online police service development.Regulation of the Head of the Indonesian National Police (Perkap) Number 9 of 2012 concerning Driving Permits related to blocking as a police measure to mark Regident data Drivers who commit violations as temporary restrictions on the legitimacy of driving a motorized vehicle need to be applied consistently. The results of the study also recommended that the local government (Pemda) provide public transportation at affordable costs by the community and cover all of its areas (including remote areas) for school children, so that there were no obstacles in transportation from home to school. Besides that, it is necessary to integrate police service data with a uniform program and format so as to facilitate data synchronization between work units within the police institution and between institutions (eg population data with police data, police data with hospital or raharja service data, etc.). It is appropriate to develop an online police service in an integrated, not partial manner so that it is connected between regions throughout the jurisdiction of the Republic of Indonesia. Penelitia ini bertujuan merekomendasikan strategi penguatan budaya etik berlalu lintas yang diharapkan dapat memberikan output berupa: Terwujudnya keamanan, keselamatan, ketertiban, kelancaran lalu lintas; Terwujudnya kinerja positif institusi kepolisian; Peningkatan kualitas hidup masyarakat. Hasil penelitian juga diharapkan dapat mempercepat integrasi antar unit pada fungsi lalu lintas guna mewujudkan optimalisasi kinerja kepolisian bidang lalu lintas, efisiensi dan efektivitas kinerja kepolisian bidang lalu lintas serta optimalisasi keselamatan jalan sehingga menurunkan: angka kecelakaan lalu lintas, potensi gangguan keamanan dan keselamatan jalan serta kemacetan lalu lintas.Fokus penelitian mencakup: Pelanggaran lalu lintas; Kendala mewujudkan Keamanan, Keselamatan, Ketertiban, Kelancaran Lalu Lintas (Kamseltibcarlantas); Strategi penguatan budaya etik berlalu lintas guna mewujudkan Kamseltibcarlantas. Berbagai kendala mewujudkan Keamanan, Keselamatan, Ketertiban, Kelancaran Lalu Lintas (Kamseltibcarlantas) mencakup beberapa aspek, yaitu: regulasi, ketersediaan transportasi umum, database dan teknologi informasi. Beberapa strategi yang dapat dikembangkan terkait penguatan budaya etik berlalu lintas adalah: a) Penetapan regulasi terkait reward and punishment pelanggar lalu lintas; b) Penyediaan dan pengembangan transportasi umum berkeselamatan; c) Pengintegrasian data dan sistem; d) Pembangunan layanan kepolisian online secara terintegrasi.Peraturan Kepala Kepolisian Negara Republik Indonesia (Perkap) Nomor 9 Tahun 2012 Tentang Surat Izin Mengemudi terkait pemblokiran sebagai tindakan kepolisian untuk memberikan tanda pada data Regident Pengemudi yang melakukan pelanggaran sebagai pembatasan sementara terhadap legitimasi mengemudikan kendaraan bermotor perlu diterapkan secara konsisten. Hasil penelitian juga merekomendasikan Pemerintah Daerah (Pemda) setempat meyediakan transportasi umum berkeselamatan berbiaya terjangkau oleh masyarakat dan mencakup seluruh daerahnya (termasuk pelosok) untuk anak-anak sekolah, sehingga tidak ada kendala transportasi dari rumah menuju sekolah. Selain itu perlu dilakukan pengintegrasian data layanan kepolisian dengan program dan format yang seragam sehingga memudahkan sinkronisasi data antar satuan kerja dilingkungan institusi kepolisian dan antar institusi (misalnya data kependudukan dengan data kepolisian, data kepolisian dengan data instansi rumah sakit atau jasa raharja dan lain sebagainya). Selayaknya pembangunan layanan kepolisian online secara terintegrasi, tidak parsial sehingga terkoneksi antar wilayah diseluruh wilayah hukum kepolisian negara Republik Indonesia.